2015
DOI: 10.1007/jhep06(2015)151
|View full text |Cite
|
Sign up to set email alerts
|

Mass insertions vs. mass eigenstates calculations in flavour physics

Abstract: We present and prove a theorem of matrix analysis, the Flavour Expansion Theorem (or FET), according to which, an analytic function of a Hermitian matrix can be expanded polynomially in terms of its off-diagonal elements with coefficients being the divided differences of the analytic function and arguments the diagonal elements of the Hermitian matrix. The theorem is applicable in case of flavour changing amplitudes. At one-loop level this procedure is particularly natural due to the observation that every loo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(49 citation statements)
references
References 38 publications
2
46
0
1
Order By: Relevance
“…Recent studies have additionally shown that the MIA results can alternatively be also obtained if one expands properly the starting expressions in the mass basis [52,53]. The main advantage of using the MIA for the one-loop computation of the Γ(H x → l klm ) partial widths (H x = h, H, A) is clear: it provides very simple analytic formulas for the form factors involved which after a proper expansion, to be valid in the case of heavy sparticle masses of our interest here, say m SUSY O(1 TeV), can be recast in simple LFV effective vertices V eff Hxlml k , and these in turn are very useful for a simplified phenomenological study of the LFVHD rates in terms of the generic δ AB mk 's and their comparison with data.…”
Section: Jhep03(2016)055mentioning
confidence: 99%
“…Recent studies have additionally shown that the MIA results can alternatively be also obtained if one expands properly the starting expressions in the mass basis [52,53]. The main advantage of using the MIA for the one-loop computation of the Γ(H x → l klm ) partial widths (H x = h, H, A) is clear: it provides very simple analytic formulas for the form factors involved which after a proper expansion, to be valid in the case of heavy sparticle masses of our interest here, say m SUSY O(1 TeV), can be recast in simple LFV effective vertices V eff Hxlml k , and these in turn are very useful for a simplified phenomenological study of the LFVHD rates in terms of the generic δ AB mk 's and their comparison with data.…”
Section: Jhep03(2016)055mentioning
confidence: 99%
“…Moreover, we have obtained an analytical expansion of the dominant gluino amplitude by using a theorem of matrix algebra [59] and have arrived at the approximate master formula (3.9). This formula worked as a guide in order to understand better the cancellations between various contributions, decoupling effects and enhancement scenarios in t → q h amplitude.…”
Section: Discussionmentioning
confidence: 99%
“…The theorem, applied first in [3], but formulated and proved in [1], suggests that any analytic function of a Hermitian matrix f (A) can be expanded polynomially in terms of the off-diagonal elements of the matrix, a property which will be shown to have an intimate connection with the MIA expansion, as discussed in what follows. In more detail, if f (A) is an analytic Hermitian matrix function, then any element of this matrix function will be given by the expansion,…”
Section: The Flavour Expansion Theorem: a Brief Reviewmentioning
confidence: 94%
“…As has been shown in [1] analogous, FET-treatable expressions are obtained from diagrams involving fermions (or gauge bosons) as well. The generalization to the multivariable case is always straightforward.…”
Section: The Flavour Expansion Theorem: a Brief Reviewmentioning
confidence: 95%
See 1 more Smart Citation